More Than a Tafsir: Convergence, Contestation, and Deradicalization of Quranic Interpretations on Website - Rosyid, Muhammad; Anoraga, Bhirawa (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
Social media has opened space for practically anyone to interpret the Qur’an, thus the contestation of tafsir cannot be avoided. The term e-tafsir in this article refers to the Quranic interpretations that appear in the digital space through new media (both website and social media). This study employs a digital ethnography method by investigating and observing various websites related to the Quranic interpretations. It focuses on popular Islamic websites such as tafsiralquran.id, ibtimes.id, and buletinkaffah.com, which regularly uploaded Islamic articles between 2020 and 2023. The research argues that social media has resulted in the proliferation of e-tafsir, including conservative (textualist) interpretations of the Qur’an. Furthermore, the author contends that to reduce radicalism in Indonesia, it is not enough to block conservative websites; it should be countered by spreading moderate Quranic interpretations. This article unveils the contestation of e-tafsir in Indonesia, which may also occur in other digitalizing Muslim worlds.